Green Synthesis and Characterization of ZnO Nanoparticles using Annona Muricata Leaves - Sergio P.R. Avila-Concepción; Fanny Samanamud Moreno; Héctor Chinchay-Espino; Gina Zavaleta-Espejo; Eiser Valle-Rivera; Evelyn Carranza-Segura; Segundo Jauregui Rosas (Chemical Engineering Transactions)
Zinc oxide (ZnO) nanoparticles were synthesized by green chemistry from aqueous extracts of Annona muricata (Soursop) leaves at different concentrations (25 g/L, 50 g/L, 100 g/L, and 200 g/L), subjected to thermal treatment at 400 °C for 1 h. The obtained nanoparticles were characterized using X-ray diffraction (XRD), UV-Vis spectroscopy, Raman spectroscopy, TEM, photoluminescence (PL) and FTIR techniques. XRD and Raman results confirmed the formation of wurtzite-phase crystallized ZnO nanoparticles with hexagonal structure. Furthermore, the average crystallite size decreased with increasing leaf concentration. The TEM result confirmed the NP size for the concentration of 100 g/L was 8 nm, being consistent with the XRD results. Also, it was determined by PL and UV-Vis that the decrease in crystallite size and band gap was correlated with a lower defect concentration and an increase in particle size. The presence of biological residues in the extract was confirmed by FTIR. It was determined that 100 g/L of A. muricata leaf was the optimal concentration to produce ZnO nanoparticles with the smallest crystallite size. In conclusion, it was demonstrated that the developed method is simple and economical, standing out compared to conventional chemical methods due to its environmentally friendly nature and the reduced use of hazardous chemicals; and it has been observed that controlling the amount of A. muricata leaves allows for a certain control over the size of the ZnO nanoparticles (NPs).